Rejuvenation of recreational park through sustainable approach at Taman Tasik Shah Alam, Selangor Darul Ehsan/ Mohd Farhan Ahmad Tarusan - Ahmad Tarusan, Mohd Farhan (2017)
This study is about transforming recreational park at Taman Tasik Shah Alam, Selangor Darul Ehsan becoming a sustainable park by using ecological approach. Rejuvenation process had being taken as the main process in considering existing feature that needs to enhance and conserve to gives a new excitement in the future. The problem statement that occurring on this topic are ecology, social space and physical. To overcome the issues, the certain objective has being taken for strengthening the finding result. Primary method and secondary method becoming major tools to gain the inventory data. The inventory is focused on physical inventory, environmental inventory, and socio-cultural inventory in order to concern sustainable criteria. Conceptual idea gain from synthesis method derives the concept of 'Green Heart' that rely on sustainable development, low impact development and heart function conceptual. The findings of this study are showing the result that towards sustainable park objective. It really important in giving the new refreshment of Taman Tasik Shah Alam rich with biodiversity in the center of the urban area. Ecological detail design really helps in support the conceptual idea in a practical way by considering the material and planting strategies for future image of the site study.